Antitumor Mechanism of the Essential Oils from Two Succulent Plants in Multidrug Resistance Leukemia Cell - Poma, Paola (Pharmaceuticals (Basel), 2019)
Drug resistance remains a major challenge in the treatment of cancer. The multiplicity of the drug resistance determinants raises the question about the optimal strategies to deal with them. Essential oils showed to inhibit the growth of different tumor cell types. Essential oils contain several chemical classes of compounds whose heterogeneity of active moieties can help prevent the development of drug resistance. In the present paper, we analyzed, by gas chromatography-mass spectrometry the chemical composition of the essential oil of the leaves of Kalanchoe beharensis obtained by hydrodistillation and compared the chemical composition of its essential oil with that of Cyphostemma juttae. Our results demonstrated the anticancer and proapoptotic activities of both species against acute myeloid leukemia on an in vitro model and its multidrug resistant variant involving NF-κB pathway. The essential oils of both species produced a significant decrease in many targets of NF-κB both at mRNA and protein levels. The results corroborate the idea that essential oils may be a good alternative to traditional drugs in the treatment of cancer, especially in drug resistant cancer.